Advantages of analyzing postmortem brain samples in routine forensic drug screening—Case series of three non-natural deaths tested positive for lysergic acid diethylamide (LSD). (September 2017) - Mardal, Marie; Johansen, Sys Stybe; Thomsen, Ragnar; Linnet, Kristian
Highlights: Three case reports of non-natural deaths, where the deceased had consumed LSD. Quantification of LSD, iso-LSD, and 2-oxo-3-hydroxy-LSD by UHPLC–MS/MS. Highest concentration levels of LSD in the target organ. Abstract: Three case reports are presented, including autopsy findings and toxicological screening results, which were tested positive for the potent hallucinogenic drug lysergic acid diethylamide (LSD). LSD and its main metabolites were quantified in brain tissue and femoral blood, and furthermore hematoma and urine when available. LSD, its main metabolite 2-oxo-3-hydroxy-LSD (oxo-HO-LSD), and iso-LSD were quantified in biological samples according to a previously published procedure involving liquid–liquid extraction and ultra-high performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS). LSD was measured in the brain tissue of all presented cases at a concentration level from 0.34–10.8 μg/kg. The concentration level in the target organ was higher than in peripheral blood. Additional psychoactive compounds were quantified in blood and brain tissue, though all below toxic concentration levels. The cause of death in case 1 was collision-induced brain injury, while it was drowning in case 2 and 3 and thus not drug intoxication. However, the toxicological findings could help explain the decedent's inability to cope with brain injury or drowning incidents. The presented findings could help establish reference concentrations in brain samples and assist in interpretation of results from forensic drug screening in brain tissue. This is to the author's knowledge the first report of LSD, iso-LSD, and oxo-HO-LSD measured in brain tissue samples.